EXPLORING URBAN PARKS: PERFORMANCE ANALYSIS AND IMPROVEMENT STRATEGIES FOR AMBEDKAR MEMORIAL PARK, LUCKNOW - Nisar, Zeba; Ashraf, Khurram; Verma, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Urban parks serve as vital green lungs for bustling cities, offering sanctuary, fostering community, and injecting life into concrete jungles. Their role in enhancing livability through recreation, environmental benefits, and social cohesion is undeniable. In Lucknow, Uttar Pradesh, stands Dr. Bhimrao Ambedkar Samajik Parivartan Prateek Sthal, popularly known as Ambedkar Park – a unique blend of public park, memorial, and architectural marvel. Sprawling across 108 acres, this majestic complex pays homage to Dr. B.R. Ambedkar, the architect of the Indian Constitution and champion of social justice, while offering a verdant escape within the city’s hustle. However, questions persist about its true contribution to urban green space and its potential for enhancing livability. This research delves into a comprehensive study of Ambedkar Park, assessing its current state and proposing strategies to revitalize it into a more vibrant and inclusive space. A mixed-methods approach, including site visits, SWOT analysis, surveys, and focus group discussions, was employed to gather comprehensive data on the park’s status and user perceptions. By highlighting existing challenges and opportunities, it ultimately leads to a discussion on potential improvements for a more vibrant and livable urban green space.